2020
DOI: 10.1186/s41983-020-00201-3
|View full text |Cite
|
Sign up to set email alerts
|

Proper timing of control of hypertension and outcome in acute spontaneous intracerebral hemorrhage

Abstract: Objective Hypertension is the commonest cause of acute spontaneous intracerebral hemorrhage (ICH) which is life-threatening with a poor prognosis. The aim of this study is to evaluate the prognosis and blood pressure monitoring and control in patients presented by acute spontaneous ICH. Methods One hundred and fifty patients presented by acute spontaneous ICH were classified according to the modified Rankin Scale (mRS) score after discharge to 70 patients with better outcomes (mRS = 0–2) while 80 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
2
7
0
1
Order By: Relevance
“…Low GCS score (<8) was associated with both higher mortality and unfavorable outcomes, which is similar to the findings of other studies from South Asia 21,27,28 . NIHSS score >14 was associated with unfavorable outcomes in our study and has also been reported by Bhatia et al 27 SBP at 24 hours was also a significant predictor of outcome in our cohort of patients, as the mean SBP in patients with unfavorable outcomes was higher than in patients with a favorable outcome [153.1±12.1 vs. 147.9±13.9 mm Hg ( P -value=0.02)], which emphasizes the importance of lowering the mean BP after SICH to improve the outcome, as recommended by studies describing the effect of controlling BP after ICH 29,30 . All risk factors, except the impaired renal function test, equally contributed to the clinical outcome in both groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Low GCS score (<8) was associated with both higher mortality and unfavorable outcomes, which is similar to the findings of other studies from South Asia 21,27,28 . NIHSS score >14 was associated with unfavorable outcomes in our study and has also been reported by Bhatia et al 27 SBP at 24 hours was also a significant predictor of outcome in our cohort of patients, as the mean SBP in patients with unfavorable outcomes was higher than in patients with a favorable outcome [153.1±12.1 vs. 147.9±13.9 mm Hg ( P -value=0.02)], which emphasizes the importance of lowering the mean BP after SICH to improve the outcome, as recommended by studies describing the effect of controlling BP after ICH 29,30 . All risk factors, except the impaired renal function test, equally contributed to the clinical outcome in both groups.…”
Section: Discussionsupporting
confidence: 91%
“…21,27,28 NIHSS score > 14 was associated with unfavorable outcomes in our study and has also been reported by Bhatia et al 27 SBP at 24 hours was also a significant predictor of outcome in our cohort of patients, as the mean SBP in patients with unfavorable outcomes was higher than in patients with a favorable outcome [153.1 12.1 vs. 147.9 13.9 mm Hg (P-value = 0.02)], which emphasizes the importance of lowering the mean BP after SICH to improve the outcome, as recommended by studies describing the effect of controlling BP after ICH. 29,30 All risk factors, except the impaired renal function test, equally contributed to the clinical outcome in both groups. A low estimated glomerular filtration rate may indicate acute renal injury or chronic kidney disease, which has been mentioned in previous studies to be associated with poor outcomes and mortality 1 year after ICH.…”
Section: Discussionmentioning
confidence: 98%
“…Though further investigation of these hypotheses is required, taken together, our evidence indicates that hypertensive aging is associated with worse ICH outcomes in this model, as observed clinically. 44,45 Regardless of strain and age, we observed widespread tissue compliance occurring in all ICH groups in our study. Indeed, this tissue compliance, estimated from contralateral hemisphere volume, accommodates at least 35.3 μL (pooled estimate with 95% CI, 17.7-52.9 μL) of mass effect, and this does not include the compliance response within intact regions of the affected ipsilateral hemisphere.…”
Section: Discussionsupporting
confidence: 47%
“…We prespecified the covariables used for adjustment in our multivariable analyses using known independent predictors of 30-day outcome after ICH, described by the ICH score which have been robustly established and validated. 3 , 34 Other variables, such as systolic blood pressure, 21 , 35 and blood glucose at initial medical assessment, as well as antithrombotic medication usage 36 , 37 and diabetes mellitus, 38 have been associated with various outcomes after ICH. However, these associations vary between reports or have not been shown to predict outcome independent of the ICH score components and were therefore not included in our multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%